Reading on Paper and Screen among Senior Adults: Cognitive Map and Technophobia - Hou, Jinghui; Wu, Yijie; Harrell, Erin (Frontiers in Psychology, 2017)
While the senior population has been increasingly engaged with reading on mobile technologies, research that specifically documents the impact of technologies on reading for this age group has still been lacking. The present study investigated how different reading media (screen versus paper) might result in different reading outcomes among older adults due to both cognitive and psychological factors. Using a laboratory experiment with eighty-one participants aged 57 to 85, our results supported past research and showed the influence of cognitive map formation on readers’ feelings of fatigue. We contributed empirical evidence to the contention that reading on a screen could match that of reading from paper if the presentation of the text on screen resemble that of the print. Our findings also suggested that individual levels of technophobia was an important barrier to older adults’ effective use of mobile technologies for reading. In the post-hoc analyses, we further showed that technophobia was correlated with technology experience, certain personality traits, and age. The present study highlights the importance of providing tailored support that helps older adults overcome psychological obstacles in using technologies.